Effective SLOPE: EffectS of Lifestyle interventions in Older PEople with obesity: a systematic review and network meta-analysis protocol. Issue 10 (7th October 2020) - Torbahn, Gabriel; Schoene, Daniel; Schwingshackl, Lukas; Rücker, Gerta; Knüttel, Helge; Kemmler, Wolfgang; Sieber, Cornel C; Batsis, John A; Villareal, Dennis T; Stroebele-Benschop, Nanette; Volkert, Dorothee; Kiesswetter, Eva
Abstract : Introduction: Obesity is highly prevalent in older adults aged 65 years or older. Different lifestyle interventions (diet, exercise, self-management) are available but benefits and harms have not been fully quantified comparing all available health promotion interventions. Special consideration must be given to functional outcomes and possible adverse effects (loss of muscle and bone mass, hypoglycaemia) of weight loss interventions in this age group. The objective of this study is to synthesise the evidence regarding the effects of different types and modalities of lifestyle interventions, or their combinations, on physical function and obesity-related outcomes such as body composition in older adults with obesity. Methods and analyses: Six databases (Medline, Embase, Cochrane Central Register of Controlled Trials, Cumulated Index to Nursing and Allied Health Literature (CINAHL), Psychinfo and Web of Science) and two trial registries (Clinicaltrials.gov and the WHO International Clinical Trials Registry Platform) will be searched for randomised controlled trials of lifestyle interventions in older adults with obesity. Screening (title/abstract and full-text) and data extraction of references as well as assessment of risk of bias and rating of the certainty of evidence (Grading of Recommendations, Assessment, Development and Evaluation for network meta-analyses) will be performed by two reviewers independently. Frequentist random-effects network meta-analyses will be conducted to determine the pooled effects from each intervention. Ethics and dissemination: We will submit our findings to peer-reviewed journals and present at national and international conferences as well as in scientific medical societies. Patient-targeted dissemination will involve local and national advocate groups. PROSPERO registration number: CRD42019147286.